Secondary care clinicians and staff have a key role in delivering equivalence of care for prisoners: A qualitative study of prisoners' experiences. (July 2020) - Edge, Chantal; Stockley, Mr Rich; Swabey, Mrs Laura; King, Mrs Emma; Decodts, Mr Fabien; Hard, Dr Jake; Black, Dr Georgia
Abstract: Background: While challenging to provide, prisoners are entitled to healthcare equivalent to community patients. This typically involves them travelling to hospitals for secondary care, whilst adhering to the prison's operational security constraints. Better understanding of equivalence issues this raises may help hospitals and prisons consider how to make services more inclusive and accessible to prisoners. We used prisoners' accounts of secondary care experiences to understand how these relate to the principle of healthcare equivalence. Methods: We undertook a qualitative interview ( n = 17) and focus group ( n = 5) study in the English prison estate. Prisoners who had visited acute hospitals for consultations were eligible for participation. They were recruited by peer researchers. 45 people (21 female, 24 male, average age 41) took part across five prisons. Participants were purposively recruited for diversity in gender, age and ethnicity. Findings: Experiences of hospital healthcare were analysed for themes relating to the principle of 'equivalence of care' using Framework Analysis. Participants described five experiences challenging 'equivalence of care' for prisoners: (1) Security overriding healthcare need or experience (2) Security creating public humiliation and fear (3) Difficulties relating to prison officer's role in medical consultations (4) Delayed access due to prison regime and transport requirements and (5) Patient autonomy restricted in management of their own healthcare. Interpretation: Achieving equivalence of care for prisoners is undermined by fear, stigma, reduced autonomy and security requirements. It requires co-ordinated action from commissioners, managers, and providers of prison and healthcare systems to address these barriers. There is a need for frontline prison and healthcare staff to address stigma and ensure they understand common issues faced by prisoners seeking to access healthcare, while developing strategies which empower the autonomy of prisoners' healthcare decisions.